PRINT AND DIGITAL-BASED ISLAMIC EDUCATION TEACHING MATERIALS: EDUCATIONAL INNOVATION IN THE DIGITAL AGE: Studi Literatur tentang Transformasi Digital dalam Pendidikan Agama Islam - Miftahul J Jannah; Salami Mahmud Salami; Nurbayani Nurbayani (STAI Nusantara Kota Banda Aceh, 2026)
This study discusses innovations in print and electronic-based learning media for Islamic Religious Education (PAI) in the digital era. Digital transformation in education requires PAI teachers to adapt to interactive and engaging learning technologies for the digital generation. This research aims to analyze the effectiveness, forms, and challenges of implementing electronic-based learning media in PAI. The research method used is library research by analyzing various literature on learning media and PAI learning innovations in the digital era. The results show that digital transformation in PAI learning includes the use of e-learning platforms, multimedia, and school management information systems that can enhance learning effectiveness. However, there are several challenges faced by teachers, including limited technology competence, lack of training, technical challenges, curriculum adjustments, and students' limited access to technology. The implementation of digital technology in PAI requires a prudent approach by considering the development of digital skills, critical thinking, collaboration, and problem-based learning to create meaningful learning experiences.